Cover Picture: The Planktonic Relationship Between Fluid‐Like Electrodes and Bacteria: Wiring in Motion (ChemSusChem 4/2017). Issue 4 (16th February 2017) - Tejedor‐Sanz, Sara; Quejigo, Jose Rodrigo; Berná, Antonio; Esteve‐Núñez, Abraham
Abstract : The Cover picture shows the bacteria‐electrode interaction between a fluid‐like electrode and planktonic living cells in a microbial electrochemical device. We show for the first time that a biofilm living mode is not a strict requirement for Geobacter sulfurreducens to perform extracellular electron transfer (EET) to an anode, an alternative to the paradigm of microbial EET in which electroactive bacteria colonize an electrically conductive surface to transfer electrons directly to it. More details can be found in the Full Paper by Tejedor‐Sanz et al. onpage 693 in Issue 4, 2017 (DOI:10.1002/cssc.201601329 ).